Clinical and psychopathological features of the course and outcome of the first psychotic episode. - Bazhora, Yuri; Gudz, Valentyn; Mozgova, Valentina; Usychenko, Kateryna; Shvets, Nikol (Journal of Education, Health and Sport, 2023)
Recently it has been established that cytokines are involved in the regulation of the body’s defense reactions in response to a pathogen and form an independent system for regulating homeostasis. The aim of this work is to study the relationship of the polymorphic marker TNFα (rs1800620) with its quantitative content and the degree of liver fibrosis in patients with various chronic hepatitis (VHC, VHB, VHB+C). The 82 patients with chronic hepatitis B, 62 patients with hepatitis B+C, and 100 patients with chronic hepatitis C were examined. GGTNFα (rs1800620) genotype is protective for patients with various viral hepatitis, and the GATNFα (rs1800620)and AATNFα (rs1800620)genotypes are profibrogenic for patients with chronic hepatitis B, chronic hepatitis B+C and chronic hepatitis C, respectively, since a high degree of fibrosis than in carriers of the homozygous GGTNFα (rs1800620)genotype. It is possible that the rate of fibrosis progression is influenced not only by the qualitative content of TNFα, but also by a certain genotype.